Tinjauan Kelengkapan Pengisian Formulir Informed Consent Pada Pasien Pra Operasi Katarak di Rumah Sakit Khusus Mata SMEC - Lovita Eka Sari Br. PA (SUAN PUBLISHER, 2024)
Medical record is a file that contains records and documents regarding identity, examination, treatment, action, and other services that have been provided to patients. The purpose of this study was to determine the percentage of completeness of the informed consent form in pre cataract surgery patients. This type of research is quantitative research that only describes the state of the object, there is no intention to generalize the results. The time of this research was carried out in June-July 2021 at the Medan SMEC Eye Specialist Hospital in 2021. In conducting this study, the researchers took a sample of 60 files. Based on the results of research conducted at the SMEC Eye Specialist Hospital, Medan, the provision of medical information was carried out entirely by authorized officers. But in providing medical information, some officers did not explain in its entirety, such as only providing 9 medical information out of 11 medical information that should be given to patients. The conclusion of this study is that the completeness of filling out the informed consent form in the medical record file at the SMEC Eye Specialist Hospital has not reached 100% complete, according to the results of the study, namely the average percentage of completeness of the types of information in the complete informed consent form is 40 (67%). and incomplete 20 (33.3%). It is hoped that the Director will conduct training on the importance of completing the informed consent form for officers